A opacidade do sofrimento humano decorrente de desastres sob a perspectiva do jornalismo humanitário - Cilene, Victor (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
Humanitarian Journalism is establishing its first foundations in the context of the largest humanitarian crisis since the end of World War II, in which there millions of people who are victims of hunger, armed conflicts, civil wars, of widespread violence, of disasters and climate changes. Albeit human suffering accompanies millions of people around the world, humanitarian institutions denounce that such suffering is beared in silence, as a result of media omission and indifference. This essay, partly written as a first-person account, adopts the precepts and ways of comprehension for telling how we aim to build a kind of journalism which is capable to reduce human suffering and, above all, to prevent reporting routines to be work for silencing and opacity, for the “veil of forgetfulness” and the “routines of normality”